The constitutional framework for enhanced cooperation in EU law - Böttner, Robert (Nijhoff studies in EU law, 2021)
"In The Constitutional Framework for Enhanced Cooperation in EU Law, the author analyses the primary-law framework of this flexibility tool. On the basis of profound literature review and against the background of recent Member State practice, the author redefines the constitutional rules of Enhanced Cooperation. He draws conclusions on this tool's legal limits, but also its potential for European integration"--